EFFECT OF STRETCHING RESPIRATORY ACCESSORY MUSCLES IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE - K, Rekha; Rai, Shristi; Anandh, Vaiyapuri; D, Samuel Sundar Doss (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To determine the effects of respiratory accessory muscles stretching in chronic obstructive pulmonary disease (COPD). Methods: A total of 30 patients with COPD were selected based on the inclusion and exclusion criteria. Group allocation was randomized and divided into two groups: Group A was treated with stretching respiratory accessory muscles and Group B was treated with conventional therapy (diaphragmatic breathing exercise and thoracic mobility exercise). All the patients were evaluated with chest expansion measurement using inch tape, dyspnea grade using modified Borg's scale, and 6 minutes walk test at baseline after which, treatment for a period of 4-week was given and same tests were repeated for post-test analysis at the end of 4 weeks. Results: There is a significant difference between pre- and post-tests mean values in both groups. Group A being highly significant with a greater difference in pre- and post-tests values with a p<0.0001 for chest expansion measurements, modified Borg's scale and 6 minutes walk test. Conclusion: This study showed that respiratory accessory muscle stretching significantly improved chest expansion, reduced dyspnea, and increase exercise tolerance level in patients with COPD. Keywords: Chronic obstructive pulmonary disease, Respiratory, Accessory muscle stretching.